2014
DOI: 10.1126/science.1239882
|View full text |Cite
|
Sign up to set email alerts
|

Development-Inspired Reprogramming of the Mammalian Central Nervous System

Abstract: In 2012, John Gurdon and Shinya Yamanaka shared the Nobel Prize for the exciting demonstration that the identity of differentiated cells is not irreversibly determined but can be changed back to a pluripotent state under appropriate instructive signals. The principle that differentiated cells can revert to an embryonic state and even be converted directly from one cell-type into another not only turns fundamental principles of development on their head but also has profound implications for regenerative medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 63 publications
1
87
0
Order By: Relevance
“…To examine the possible physiological relevance of gene expression deficiencies in CSB-deficient cells, we investigated cellular reprogramming of fibroblasts to neurons (13). This approach has previously been used to study diseases such as Alzheimer's disease (14) and Parkinson disease (15).…”
Section: Csb Is Required For Transdifferentiation Of Fibroblasts To Nmentioning
confidence: 99%
“…To examine the possible physiological relevance of gene expression deficiencies in CSB-deficient cells, we investigated cellular reprogramming of fibroblasts to neurons (13). This approach has previously been used to study diseases such as Alzheimer's disease (14) and Parkinson disease (15).…”
Section: Csb Is Required For Transdifferentiation Of Fibroblasts To Nmentioning
confidence: 99%
“…The extraordinary interest in SoxB1 proteins and in particular the pluripotency factor Sox2 [SRY (sex determining region Y)-box 2] rests on a multitude of functional implications concerning basic and applied biomedical problems: it promotes neuroectodermal lineage selection in ES cells (Zhao et al 2004;Thomson et al 2011), plays a major role in reprogramming of non-neural cells to neural stem or precursor cells (Maucksch et al 2013;Amamoto and Arlotta 2014), is critically involved in vertebrate neurogenesis and glial cell development (Reiprich and Wegner, this issue;Hoffmann et al 2014), and orthologous proteins are found in the neurogenic regions of all animal phyla analyzed (see below). SOX2 haploinsufficiency in humans is associated with brain malformations as well as defects in multiple sensory systems including anophthalmia and hearing loss (Fantes et al 2003;Hagstrom et al 2005;Zenteno et al 2005).…”
Section: Sodium Channel Gene Expression and The Quest For The Master mentioning
confidence: 99%
“…The first concerns the critical issue of unambiguous identification of a cell as being a neuron. On the other hand, it is currently not clear to which extent procedures to program neurons in vitro do and need to resemble in vivo development (Amamoto and Arlotta 2014).…”
mentioning
confidence: 99%